Pengaruh Kreativitas Verbal terhadap Keterampilan Berbicara pada Mahasiswa Program Studi Psikologi Universitas Negeri Manado - Tellma M. Tiwa (Peneliti.net, 2023)
Verbal creativity is one of the factors that can support a person's speaking skills apart from other factors. Speaking skills are the ability to express thoughts and ideas in the mind accompanied by good speaking expression and conveying ideas. The aim of this research is to find out whether there is an influence of verbal creativity on speaking skills in psychology students at Manado State University. In this research, quantitative correlational research was used. The subjects in this research were psychology study program students in semesters III and V, class of 2015 and 2016. The sampling technique used was cluster random sampling of 10%. And the total sample size was 38 psychology students. The instruments used were verbal creativity tests and speaking skills scales. And in this research, the data analysis technique used in hypothesis testing is a simple regression analysis technique by testing the data using the SPSS 24.0 for Windows tool. The results of this research showed that